Analysis of the Effect of Phacoemulsification and Intraocular Lens Implantation Combined With Trabeculectomy on Cataract and Its Influence on Corneal Endothelium - Wang, Bin; Tang, Liqin (Frontiers in Surgery, 2022)
Abstract Objective:To discuss the effect of phacoemulsification and intraocular lens implantation (PHACO+IOL) combined with trabeculectomy (TRAB) on cataract and its influence on corneal endothelium. Methods:120 cataract patients admitted to our hospital from January 2018 to January 2021 were selected. According to different surgical methods, they were divided into control group and observation group. The observation group was treated with PHACO+IOL combined with TRAB, the control group only received PHACO. The clinical effect, ophthalmic related parameters, corneal endothelium, complications, satisfaction of two groups were observed. Results:The total effective rate and total satisfaction rate of the observation group were significantly higher than the control group (P<0.05). 1 month after operation, the vision and central anterior chamber depth of the observation group were higher than those of the control group, and intraocular pressure (IOP) was lower than that of the control group (P<0.05). 1 month after operation, the corneal endothelial cell area and cell density in the observation group were not significantly different from those before operation (P>0.05). There was no significant difference in the total incidence of complications between the two groups (P>0.05). Conclusion:PHACO+IOL combined with TRAB has a good curative effect in the treatment of cataract, which can improve the patients' vision and IOP, keep the functional integrity of corneal endothelial cells, and does not increase the occurrence of complications, the patients' satisfaction is high.